Negation, subjectivity, and the history of rhetoric - Vitanza, Victor J. (State University of New York Press, 1997)
Vitanza introduces his book with the questions: "What Do I Want, Wanting to Write This ('our') Book? What Do I Want, Wanting You to Read This ('our') Book?" Thereafter, in a series of chapters and excursions and as schizographer of rhetorics (erotics), he interrogates three recent, influential historians of Sophists (Edward Schiappa, John Poulakos, and Susan Jarratt), and how these historians as well as others represent Sophists and, in particular, Isocrates and Gorgias under the sign of the negative. Vitanza concludes - rather rebegins in a sophistic-performative excursus - with a prelude to future (anterior) histories of rhetorics. Vitanza asks: "What will have been anti-Oedipalizedized (de-negated) hysteries of rhetorics? What will have they looked like, sounded, read like? Or to ask affirmatively, what, then, will have libidinalized-hysteries of rhetorics looked, sounded, read like?"